Acute clinical signs and outcome of concussion in National Hockey League (NHL) players. Issue 5 (11th March 2013) - Comper, Paul; Hutchison, Michael
Abstract : Objectives: To describe and quantify the acute clinical signs of concussion in National Hockey League (NHL) players. Setting: National Hockey League (NHL). Design: Prospective case series of concussions over a 5 year period of regular season NHL games (2006–2011). Subjects: Digital video images of 341 NHL players diagnosed with concussions. Outcome Measures: Primary outcome measures were mechanism of contact (direct vs indirect trauma), observable acute clinical signs (eg, disorientation, loss of consciousness, balance difficulties, 'slow to get up'), and time loss that is, time between the injury and medical clearance by the physician to return to competitive play). Results: Approximately 20% of players diagnosed with concussions showed no on-ice clinical signs. Most frequent on-ice clinical signs were: (1) slow to get up; (2) clutching of the head/helmet; and (3) disorientation/dazed. The number of players with observable on-ice clinical signs, particularly for those who either sustained 'Possible/Probable Loss of Consciousness' declined following the 2009 season. None of the clinical signs predicted poor outcome (eg, greater than 21 days of time loss). Conclusions: Concussion can produce a spectrum of acute on-ice clinical signs. Most commonly observed with the 5 year sample of NHL players were 'slow to get up', 'clutching of the head/helmet', and 'disorientation/dazed'. Length of time to recovery was not predicted on the basis of acute observable signs. Competing interests: One of the authors (PC) is a paid consultant for the National Hockey League Players' Association (NHLPA).